An unusual case of syncope (International Journal of Students' Research, 2018)
Early repolarization syndrome (ERS) is a common electrocardiography (ECG) variant which may prove to be an indicator of increased long‑term cardiac mortality in general population. Although the condition is usually considered to be benign, potential arrhythmogenicity of it has been suggested by experimental studies. ERS involving inferolateral leads in the ECG has been seen to be associated with syncopal attacks or sudden cardiac death in young healthy persons. Here, we report a rare case of young asymptomatic healthy male who presented with syncope while at rest and sinus bradycardia with incidental findings of ERS on ECG.
Keywords: Electrocardiography; sudden cardiac death; syncope